Analisis Pengaruh Aglomerasi Industri, Jumlah Penduduk terhadap Tingkat Disparitas Pendapatan antar Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2016-2020 - Agnesa Marytha Chrisetyoningrum (Universitas Diponegoro, 2022)
This study aims to determine the level of inequality between regencies/cities in Central Java Province, and the influence of industrial agglomeration, population on income disparities in Central Java Province. The data used in this study is secondary data from the Central Statistics Agency (BPS) 2016-2020. The analytical method used is descriptive and regression. Regression analysis using panel data. Economic disparities are calculated by the Williamson Index. The effect of industrial agglomeration and population on income disparity was analyzed using linear regression fixed effect model. The Williamson index value for all districts/cities shows economic inequality that occurs in low criteria, except for Brebes district with moderate criteria. Industrial agglomeration variables and population have a simultaneous effect on income disparities in Central Java Province.